(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical and paraclinical characteristics and to investigate the correlation between NT-ProBNP and the severity assessment indices PSI and CURB-65 in patients with community-acquired pneumonia at Thong Nhat Hospital. Subjects and Methods: A cross-sectional descriptive study of 60 patients with communityacquired pneumonia hospitalized from January 2024 to June 2024 in the Intensive Care and Toxicology Department and the Respiratory Medicine Department. Results: The average age was 77 ± 38 years, with males accounting for 55%. At the time of admission, the PSI score was 95.1 ± 26.1, and the CURB-65 score was 1.8 ± 0.8. The average NT-ProBNP value was 675 ± 399.6 (ng/mL). Clinical symptoms included fever (43%), cough (57%), chest pain (23%), productive cough (100%), respiratory failure (32%), and mechanical ventilation (13%). In terms of laboratory findings, 50% of patients had a white blood cell count > 12 (x 10³/µL), and 48% showed signs of lobar pneumonia on chest X-ray. NT-ProBNP had a moderate positive correlation with CURB-65 (r = 0.39; p = 0.002) and a weak positive correlation with the PSI score (r = 0.22; p = 0.095). Conclusion: Patients with community-acquired pneumonia often present with atypical clinical symptoms, primarily lobar pneumonia. At the time of admission, NT-ProBNP had a moderate positive correlation with CURB-65 and a weak positive correlation with the PSI score. Therefore, NT-ProBNP may be considered a useful indicator for assessing severity to determine the appropriate treatment department for patients.